ANALISIS FLYPAPER EFFECT DANA TRANSFER DAN PAD TERHADAP BELANJADAERAH KABUPATEN/KOTA DI JAWA TIMUR - Thomas David Santosa, Rony Kurniawan, Sigit Ratnanto, Danang Wahyu Widodo & (Master of Public Administration, Universitas Slamet Riyadi, 2019)
This study examines the level of dependence (flypaper effect) and theeffect of regional transfer funds, in this case the General AllocationFund (DAU), Special Allocation Funds (DAK) and Regional OriginalIncome (PAD) for Regional Expenditures. While the location of thestudy was conducted in nine cities and 29 districts in the East Javaregion of the 2010-2017 series.Based on the t test (partial) the regional transfer funds consisting of theGeneral Allocation Fund (DAU), Special Allocation Fund (DAK) andRegional Original Revenue (PAD) have a positive and significant effecton regional expenditure (Regional Expenditure). This means that theexistence of DAU, DAK and PAD in each city and district contributesto the ability to increase regional spending,However, in the analysis of the dependence of the budget from 38districts and cities, only four cities / districts did not show symptoms ofthe fly paper effect, namely Malang City, Surabaya City, TulungagungCity and Jember. While 34 cities / regencies show symptoms ofbudgetary dependence from central transfer funds or symptoms offlypaper effects. This symptom of the flypaper effect is caused by theaccumulation of regional budget in 34 cities and districts, thecomposition of the contribution of PAD is lower than DAU and DAK.Suggestions from researchers for 34 cities / regencies in East Java tooptimize development transfer fund assistance in accordance with LawNo. 33/2004 in order to improve financial capacity and regionalindependence in development spending. The way the RegionalGovernment / District Government that experiences the symptoms ofthe flypaper effect allocates transfer funds is oriented towardsincreasing and developing economic potential in their respectiveregions,Keywords: Flypapaer Effect, Transfer Funds, Regional Original Income andRegional Expenditures